Strategic Management and Organisational Dynamics: The Challenge of Complexity - and Stacey, Ralph D. (Pitman, 2000)
In the third edition of this successful text, Ralph Stacey continues to question the view that organisations operate and succeed in relatively stable environments. He argues that in order to succeed in uncertainty and continual change, organisations need to create new perspectives and learn from the chaos within which they operate. This edition continues to focus on this radically different approach to strategic management. The central tenets of this approach have to do with unpredictability and the limitations of control, and therefore it argues against the rational models of planning and control covered in other strategy textbooks. This is done by emphasising the importance of narrative, conversation and learning from one's own experience as the central means by which we can gain understanding and knowledge of strategy in organisations. - Sharper distinction between systemic and process thinking with new chapters on the philosophical origins of systems and process thinking, second order and critical system thinking. - new material on theory of complex responsive processes, particularly to do with control, leadership and ethics. - Includes 7 management narratives, ie, personal ac
Keywords: Organizational Behavior; Strategic Planning